2023
DOI: 10.1126/scitranslmed.add9012
|View full text |Cite
|
Sign up to set email alerts
|

Malaria-driven expansion of adaptive-like functional CD56-negative NK cells correlates with clinical immunity to malaria

Abstract: Natural killer (NK) cells likely play an important role in immunity to malaria, but the effect of repeated malaria on NK cell responses remains unclear. Here, we comprehensively profiled the NK cell response in a cohort of 264 Ugandan children. Repeated malaria exposure was associated with expansion of an atypical, CD56 neg population of NK cells that differed transcriptionally, epigenetically, and phenotypically from CD56 dim NK cells, including decreased expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 63 publications
3
23
0
Order By: Relevance
“…To explore how HCMV exposure in utero influences host immune cell compartments, we performed multiparameter flow cytometry and transcriptional profiling of NK and T cells in an available subset of cord blood samples from cCMV+ (n=21) and cCMV-(n=20) neonates. Total NK cells and 3 major NK cell subsets including CD56 neg CD16 + , CD56 bright CD16 +/- , and CD56 dim CD16 +/- NK cells (Ty et al, 2023; Vaaben et al ., 2022) were compared in cCMV+ versus cCMV-neonates ( Fig. 2A ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To explore how HCMV exposure in utero influences host immune cell compartments, we performed multiparameter flow cytometry and transcriptional profiling of NK and T cells in an available subset of cord blood samples from cCMV+ (n=21) and cCMV-(n=20) neonates. Total NK cells and 3 major NK cell subsets including CD56 neg CD16 + , CD56 bright CD16 +/- , and CD56 dim CD16 +/- NK cells (Ty et al, 2023; Vaaben et al ., 2022) were compared in cCMV+ versus cCMV-neonates ( Fig. 2A ).…”
Section: Resultsmentioning
confidence: 99%
“…2F-G ) with enriched gene ontology pathways including innate immune response ( P adj = 1.0×10 −4 ), defense response to virus ( P adj = 2.5×10 −4 ), and type I interferon signaling ( P adj = 6.7×10 −4 ). Expression of LAG3, a checkpoint inhibitor induced by type I IFN that is highly expressed on ADCC-mediating CD56 neg CD16 + NK cells (Ty et al ., 2023), was 4-fold higher in NK cells from cCMV+ versus cCMV-neonates ( P FDR = 2.53×10 −10 ). JAKMIP1, a marker of adaptive NK cells in chronic HCMV infection (Rückert et al, 2022) was also elevated 5-fold ( P FDR = 2.53×10 −3 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro studies have recently highlighted the ability of NK cells to destroy malaria parasite-infected RBCs, with recognition mediated by antibodies targeting iRBC surface proteins 26 . Recent epidemiological studies conducted in Ugandan children have shown that repeated infections with P. falciparum alter the composition of NK cell populations, resulting in an increase in the ratio of CD56neg NK cells 27 . These CD56neg NK cells represent an atypical subset of NK cells distinct from the typical CD56dim NK cells and exhibit stronger ADCC activity compared to CD56dim NK cells, perhaps improving NK cell mediated iRBC clearance.…”
Section: Discussionmentioning
confidence: 99%
“…The IMRAS whole-blood transcriptomic studies revealed that the protection status was associated with different timing, magnitude, and nature of NK cell-related genes early after immunization. 25 The role of NK cells in malaria immunity, specifically in the antibody-mediated immunity, 50 , 51 has been recently spotlighted in Kenya and Uganda, 52 , 53 showing a potential link between the maintenance of a subset of natural killer cells (CD56 negative) and the successful control of malaria infection. 53 …”
Section: Discussionmentioning
confidence: 99%